ATOMIC ABSORPTION SPECTROSCOPY ANALYSIS OF HEAVY METALS IN WATER AT MAI-GANGA COAL MINING VILLAGE, GOMBE STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This study was designed to detect heavy metals level in water collected from Mai-ganga Coal mining village, Gombe State, North-East Nigeria. Samples was analyzed using Atomic Absorption Spectroscopy. The level of Pb, Ni, Cd, Co, Cu, Mn, Mg, Zn, and Fe were assessed. The result shows significant level of Pb at 1.833 mg/l and 5mg/l for Fe which exceeded the WHO limit (0.01 mg/l). Cu, Cr, Zn, Mn, and mg found at 0.2193, 0.4285, 0.5294, 1.60, and 3.50 mg/l respectively. Cd, and Ni were detected at 0.001mg/l and 0.002 mg/l respectively. Co was only detected in surface water (Mai-ganga earth dam) in all the samples collected. Cd, Mg, Ni, and Zn were found below the WHO, USEPA limits. Pb, Fe were found to exceed the recommended limits. Therefore, this study seeks to enlighten the mining community about the risk of heavy metals and the need by the government/mining industries to provide alternatives for Mai-ganga drinking water
Keywords: Borehole, Earth dam, World Health Organization, Drinking water, Mai-ganga Village